2011
DOI: 10.1103/physrevlett.106.126802
|View full text |Cite
|
Sign up to set email alerts
|

Single-Layer Behavior and Its Breakdown in Twisted Graphene Layers

Abstract: We report high magnetic field scanning tunneling microscopy and Landau level spectroscopy of twisted graphene layers grown by chemical vapor deposition. For twist angles exceeding ~3° the low energy carriers exhibit Landau level spectra characteristic of massless Dirac fermions. Above 20° the layers effectively decouple and the electronic properties are indistinguishable from those in single-layer graphene, while for smaller angles we observe a slowdown of the carrier velocity which is strongly angle dependent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

60
697
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(762 citation statements)
references
References 32 publications
60
697
3
2
Order By: Relevance
“…This is due to the complete decoupling of layers with a higher twist angle. 14,29 The shape and intensity of the 2D peak are characteristically different for SLG, AB stacked and twisted BLG. Hence, to ensure the nature of layer stacking in CVD grown BLG, the analysis of curve fitting for the 2D peak was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the complete decoupling of layers with a higher twist angle. 14,29 The shape and intensity of the 2D peak are characteristically different for SLG, AB stacked and twisted BLG. Hence, to ensure the nature of layer stacking in CVD grown BLG, the analysis of curve fitting for the 2D peak was performed.…”
Section: Resultsmentioning
confidence: 99%
“…When the twist angle between the stacked layers is more than 3 degrees, the charge carrier shows the characteristics of massless Dirac fermions, but with smaller carrier velocity and when this angle exceeds 20 degrees, the layers get completely decoupled, consequently their electronic properties become indistinguishable from the SLG. 14 In recent times, for graphene growth by the CVD technique there has been worldwide interest in understanding the growth mechanism to find out the ways to control it. [15][16][17][18][19][20][21][22] The self-limiting effect of low pressure CVD growth of single layer graphene on copper vanishes when the set growth conditions are outside the optimized window and the percentage growth of SLG, BLG or FLG can vary with growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For TG with small twist angles (yo15°), the experimental studies showed 1,3,6,9 that the Dirac cones for each layer persist but van Hove singularities are present due to the interlayer interaction. For large twist angles, the twisted layers effectively de-couple from each other and become indistinguishable from SLG 7 . However, several theoretical reports have recently predicted the existence of coupling between large-angle twisted layers.…”
mentioning
confidence: 99%
“…T he rotational stacking of graphene layers alters their electronic characteristics resulting in novel and rich physics [1][2][3][4][5][6][7][8] . Bernal (AB)-stacked graphene rotated by 60°b etween adjacent layers is well understood and its electronic properties are radically different from single-layer graphene (SLG).…”
mentioning
confidence: 99%
“…These heterogeneous stacks have unusual properties that are not present in individual layers and encompass a wide spectrum of physical and chemical phenomena exemplified by new van Hove singularities [4][5][6][7] , Fermi velocity renormalization 8,9 , unconventional quantum Hall effects 10 , Hofstadter's butterfly pattern [11][12][13][14] , and others. Peculiar electronic [15][16][17] and optoelectronic properties 18,19 have been revealed in diverse 2D heterostructures based on layered materials such as GR, semiconducting transition metal dichalcogenides (TMDs) and insulating hexagonal boron nitride (h-BN).…”
mentioning
confidence: 99%